Protecting And Promoting the Value of Intangible Cultural Heritage in Vietnam: Achievements and Contemporary Challenges - Phuong, Nguyen Tri (Journal of Posthumanism, 2025)
This article analyzes the current state of protecting and promoting the value of intangible cultural heritage (ICH) in Vietnam, based on the theoretical framework of the 2003 UNESCO Convention and theories on sustainable cultural development and community-based approaches. Through a mixed-methods approach, combining secondary document analysis and quantitative statistics, the study highlights Vietnam’s notable achievements in developing a legal framework, conducting inventories, documenting, inscribing heritage elements, transmitting traditional knowledge, honoring artisans, and utilizing ICH in tourism and education. However, the paper also identifies several critical limitations, such as the gap between policy and implementation, the risk of commercialization and distortion of ICH values, and the underutilization of community roles. Accordingly, the article proposes solutions to enhance the effectiveness of ICH safeguarding and promotion in the context of globalization and modernization.